Parent experiences with paediatric allergy pathways in the West Midlands: A qualitative study. Issue 3 (11th February 2019) - Diwakar, Lavanya; Cummins, Carole; Hackett, Scott; Rees, Martyn; Charles, Lynette; Kerrigan, Caroline; Creed, Helen; Roberts, Tracy
Summary: Background: The prevalence, severity and complexity of allergic diseases have been increasing steadily in the United Kingdom over the last few decades. Primary care physicians are often not adequately trained in allergy management while specialist services for allergy are scarce and heterogeneous. Services, therefore, have been unable to meet the rising demand. This is particularly true for paediatric allergy services in the United Kingdom. Objective: To understand parent experiences with paediatric allergy pathways in the West Midlands (WM) region of the United Kingdom. Methods: Parents of children aged between 0 and 16 years from the WM region were recruited opportunistically until thematic saturation was achieved. Eighteen semi‐structured interviews were carried out and transcribed verbatim. Data were analysed on NVivo software using the framework method. Themes were identified from the transcripts as well as from existing literature. Results: Parents highlighted numerous issues related to allergy services in the region including difficulties with being taken seriously by their physicians, problems with accessing health care and issues with information and the need for additional supportive care for allergies. Conclusions and Clinical relevance: Primary care for children with allergies in the WM is disparate. Parents experience difficulties in accessing primary and secondary care services and also obtaining timely and appropriate information regarding their child's allergies. Most parents were happy to be reviewed by either specialist nurses or by consultants in the hospital. Improving accessibility and availability of reliable information as well as provision of additional services (such as psychologists and dietetics) were highlighted by parents as being important to allergy services in the region. These findings can help inform future planning and commissioning of allergy services.